2009
DOI: 10.1097/crd.0b013e31819f1a83
|View full text |Cite
|
Sign up to set email alerts
|

Hemolysis Associated With Prosthetic Heart Valves

Abstract: Hemolysis is one of the potentially serious complications of prosthetic heart valves. It is usually associated with either structural deterioration or paravalvular leak. Mild, compensated hemolysis associated with mechanical heart valves is not uncommon even in the current era. Severe hemolysis is rare, however, and usually reflects paravalvular leak. The use of transesophageal echocardiography-guided operative techniques may help prevent or minimize early postoperative paravalvular leakage. There is a gamut o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(50 citation statements)
references
References 50 publications
2
42
1
Order By: Relevance
“…This might be owing to the fact that we avoided the continuous suture technique, which has proved to be associated with a high incidence of PVL after MVR [2,7]. In addition to suture technique, previous studies suggested that the presence of heavy annular calcification, small body surface area, and size and type of prosthetic valve were associated with mitral PVL [1,2,[7][8][9][10]. In the present study, however, we could not demonstrate that such factors are associated with incidence of mitral PVL.…”
Section: Commentcontrasting
confidence: 75%
“…This might be owing to the fact that we avoided the continuous suture technique, which has proved to be associated with a high incidence of PVL after MVR [2,7]. In addition to suture technique, previous studies suggested that the presence of heavy annular calcification, small body surface area, and size and type of prosthetic valve were associated with mitral PVL [1,2,[7][8][9][10]. In the present study, however, we could not demonstrate that such factors are associated with incidence of mitral PVL.…”
Section: Commentcontrasting
confidence: 75%
“…Despite a significantly higher incidence of trivial to moderate paravalvular leaks in patients after transcatheter valve implantation as compared to surgical patients, transcatheter valve patients have significantly better hemodynamics and improvement of left ventricular function (35)(36)(37). Whether paravalvular leaks after TAVI result in (clinically relevant) hemolysis (as described from surgical collectives (38)) needs further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…RBCs that have a short lifespan secondary to destruction (i.e., hemolytic anemia, 17 destruction through the passage of abnormal heart valves, 18 or splenomegaly) will result in a low A1C independent of the mean serum glucose. This situation is also present in circumstances in which the bone marrow increases the production of young RBCs (reticulocytes), as seen in patients with chronic kidney disease (CKD) who receive erythropoietin treatment for anemia; post-hemorrhage, as the healthy bone marrow is stimulated by hypoxia; or after a blood transfusion.…”
Section: Rbc Lifespanmentioning
confidence: 99%